Toxicity testings of isolated Bacillus sp. against mosquito larvae in the laboratory - Sugeng Juwono Mardihusodo Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
Studies on the spectrum of insecticidal activities of any entomopathogens indigenously obtained from any mosquito larval habitats should be accomplished to realize its recpective degree of potency and specificity as a biological control agent.These studies aimed at testing of comparative toxicides of four bacilli isolates: B. sphaericus I (23A), B. sphaericus11 (51C), B. pumilus (25C) and B. cereus (142A) against Cul= quingu.efasciatus, Aedes aegypti and Anopheles aconitus larvae in laboratory conditions.Pathogenicity and toxicity testings were undertaken after the four bacilli isolates and their controls (B. thuringiensis H-14 and B. sphaericus 1593) being cultured in slant media or produced through fermentations with a defined medium (Prof Sam Singer) as final whole cultures (FWCs) and primary powders. Titrations of all primary powders produced were carried out against standard powders of B. t. H-14 (IPS 82) and B. sphaericus 1593 (RB 80).The results of the testings showed that:1. the four bacilli isolates were respectively pathogenic for Cx. quinquefasciatus, Ae. aegypti and An. aconitus larvae;2. the degree of sensitivities of the three species of mosquito larvae against the four bacilli isolates from higher to lower levels were Cx. quinquefasciatus, Ae. aegypti and An. am-nib's;3. toxicides of the four bacilli isolates were still much lower than that of either B. t. H-14 or B. sphaericus 1593, and4. results of the attempts of primary powder production with a Sam Singer's medium for the four isolates, B. I. H-14 and B. sphaericus 1593 were considered satisfactory.Key Words: entomopathogens - bacilli isolates - B. thuringiensisH-14 - B. sphaericus 1593 - biological